Clinical relevance of high–intermediate risk endometrial cancer according to European risk classification. Issue 10 (18th August 2020) - Rychlik, Agnieszka; Zapardiel, Ignacio; Baquedano, Laura; Martínez Maestre, María Ángeles; Querleu, Denis; Coronado Martín, Pluvio J
Abstract : Objective: Risk models in endometrial cancer define prognosis and indicate adjuvant therapy. One of the currently used classifications was designed in 2016 in collaboration with the European Society of Medical Oncology (ESMO), the European Society of Gynecologic Oncology (ESGO), and the European Society of Radiotherapy (ESTRO). A high–intermediate risk group was introduced within the intermediate risk group. The purpose of this study was to evaluate the clinical relevance of this subclassification. Methods: A multicenter retrospective study was carried out at five international tertiary institutions. Patients diagnosed with intermediate risk endometrial cancer on the basis of definitive pathology findings were included. Patients were stratified into intermediate and high–intermediate risk groups. Incidence of nodal metastases, and disease free and overall survival were compared between the two risk groups in univariate and multivariate analysis. Results: 477 patients were included: 325 (68%) patients were identified as intermediate and 152 (32%) as high–intermediate endometrial cancer patients. Nodal metastases were found in 18 patients (11.8%) in the high–intermediate risk endometrial cancer group and 16 patients (4.9%) in the intermediate risk group. Lymphovascular space invasion was found to be a strong predictive factor of lymph node involvement. High–intermediate risk was found to be an independent factor of disease free survival (hazard ratio (HR) 1.76; 95% confidence interval (CI) 1.00 to 3.08; p=0.050) and overall survival (HR 1.99; 95% CI 1.10 to 3.60; p=0.022) in the multivariate analysis. Conclusions: The study validates the clinical significance of the intermediate risk endometrial cancer subclassification. Prognosis for high–intermediate risk endometrial cancer was significantly poorer. The prevalence of lymph node metastases was higher in this group of patients.